Microclimate, soil chemistry, and microbiota fail to explain Euphorbia dendroides Janzen‐Connell pattern in a shrubland. Issue 12 (4th December 2022) - Idbella, Mohamed; Abd‐ElGawad, Ahmed M.; Mazzoleni, Stefano; Bonanomi, Giuliano
Abstract: Negative plant–soil feedback can cause density and distance effects that lead to Janzen–Connell (JC) distribution. The JC hypothesis has been proposed to explain the high species diversity in tropical forests, but it has been rarely tested in species‐rich Mediterranean shrublands. In this study, we assessed whether the JC hypothesis could explain Euphorbia dendroides recruitment pattern under conspecific conditions, that is, mother plant and the canopy of Pistacia lentiscus, Juniperus phoenicea, Myrtus communis, Rosmarinus officinalis, and Olea europaea . We examined whether soil chemistry and/or soil microbiota, characterized by both bacterial and fungal communities, explained the observed JC pattern. We also explored differences in microclimate among shrub species by monitoring air temperature and light availability at different times of the year. Euphorbia recruits were almost absent under the canopy of conspecifics, being more abundant at the edge of the canopy, which fits the JC pattern. Interestingly, we also found a high density of Euphorbia recruitment under heterospecific canopies, that is, O. europaea and J. phoenicea, but a very low density under other heterospecific canopies, for example, R. officinalis and P. lentiscus . Although shrubs have a species‐specific microbiota signature under their canopy, neither the accumulation of species‐specific pathogens nor soil chemical properties explain the observed JC pattern. Despite finding that shrubs buffer high temperatures in summer, the observed microclimatic difference failed to explain the recruitment pattern. We conclude that JC is prevalent in this species‐rich Mediterranean shrubland, but the underlying mechanism remains to be investigated and clarified.